Literatura de cordel e migração nordestina: tradição e deslocamento - Luciany Aparecida Alves Santos (Estudos de Literatura Brasileira Contemporânea)
Seen as the origin, that is, the archaic, the cordel literature was almost always analyzed departing from the point of view of recovering, regaining the primitive roots of Brazilian literature. The aim of this work is to investigate how, through cultural dislocations, cordel literature is produced and discussed. By cultural dislocation we understand the migratory movement of people from the Northeast to Southeast Brazil, and the cultural relationships that follow such process. We analyze how these migratory movements influenced the poetic writing of the authors involved in such movements, and their consequences on the theoretical discussions on cordel literature.